Molecular characterisation of leeches (Clitellata, Annelida) based on the mitochondrial cytochrome oxidase I (COI) gene region for Turkish fauna - Ayhan, Hueseyin; Saglam, Naim; Mollahaliloglu, Salih; Carhan, Ahmet (Taylor & Francis Ltd, 2024)
Leeches, classified under Hirudinea within the phylum Annelida, hold a crucial position within the aquatic ecosystem due to their substantial contribution to the intricate food web. As a result of some morphological and phylogenetic uncertainties in the classification, molecular studies have been implemented in leech taxonomy. We investigated the leech fauna in 14 wetlands in the province of Ankara in the Central Anatolia Region of Turkey between 2017 and 2019. A total of 38 specimens were collected from wetlands, representing two families, four genera, and five species (Glossiphonia complanata, Glossiphonia concolor, Helobdella stagnalis, Hirudo verbana, Limnatis paluda). Morphological characters were identified following examination under a stereomicroscope, and maximum likelihood (ML), neighbour-joining (NJ) and Bayesian inference (BI) analyses were employed to resolve the phylogenetic relationships using mitochondrial cytochrome c oxidase subunit I (COI). The haplotype analysis of the obtained COI region on 15 sequences revealed 11 haplotypes.
Keywords: biodiversity